PENGEMASAN PAKET EKOWISATA DI DESA LIANG NDARA, KECAMATAN MBELILING, KABUPATEN MANGGARAI BARAT, FLORES, NUSA TENGGARA TIMUR - Charles Bertomi; Ni Made Oka Karini; I Putu Sudana (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2015)
Liang Ndara village is one of the village in Mbeliling sub-district, West Manggarai regency, Flores of East Nusa Tenggara Province. Liang Ndara village has many tourism potentials specifically regarding to the ecotourism. Free entrance fee in to those tourism places caused by unserious and less attention of the government are becoming problem, as well as Lack of human resources of people is another problem causing the potentials are not well organized yet and even it is not in a good tourism packaging. The research aim to find out the tourism potential that can be made ecotourism packages and packaging them to become an ecotourism in Liang Ndara village. The data collection of this research is by an observation, documentation, interviewing and as well as literature. The data analysis technic used is by analysis technic of qualitative descriptive. The results of this research showed that Liang Ndara village has three kinds of tourism potential which is in a packaging of ecotourism. Those potentials are the natural tourism potentials consist of Mbeliling Mountain, Cunca rami waterfall, Cunca Wae Kantor waterfall and Liang Niki Cave. The cultural tourism potentials are Caci dance, Compang Kafir Stone, Compang Serani statue, Batu Tiga, Hand Weaving of Songke, Farming Activities such as sopi/arak filtration, cultivating of rice field. Man made tourism potentials are information center in the village, guest house, and souvenir shops. The potentials above are packaged in to two kind of ecotourism packages they are Liang Ndara Village Tour and Mbeliling Green Forest Tour. The suggestions are the government is supposed to put their eyes on to develop those potential exist and need to be hand in hand with the tourism actors as well as the society. The travel agencies are expected to make an interesting tourism package like ecotourism and also supposed to be together with the society to take care and survive the tourism potentials existed.